Linguistic landscape in the Glodok Chinatown area - Jihan Luthfun Nisa; Badri Salam; Dewi Yanti; Woro Januarti; Sri Hartati (Universitas Islam Malang, 2026)
Language functions not only as a means of communication but also as a cultural marker that is visibly manifested in public spaces through the linguistic landscape (LL). Previous LL studies in Indonesia have focused on locations such as airports, train stations, and cemeteries, while Glodok Chinatown, the oldest Chinese settlement in Jakarta, has received limited scholarly attention. This study aims to (1) identify the dominant languages used on public signage in Glodok and (2) analyze how language choices reflect socio-cultural identity in the area. Employing a qualitative descriptive approach, 67 public signs were documented and analyzed using a linguistic landscape categorization framework. The findings indicate that bilingual signage dominates the area (47.76%), particularly Indonesian–Mandarin combinations, followed by monolingual signs (44.78%) and multilingual signs (7.46%). Indonesian functions as a unifying national language, while Mandarin symbolizes the preservation of the Chinese ethnic heritage. The presence of English and other languages such as Japanese, Korean, Arabic, and Minangkabau reflects Glodok’s multicultural character and its engagement with globalization and economic activities. These patterns demonstrate that Glodok’s linguistic landscape operates not only as a communicative tool but also as a symbolic space where cultural identity negotiation, identity maintenance, and economic considerations intersect. By examining a historically multicultural district, this study contributes empirical evidence to linguistic landscape research and situates Glodok within broader discussions of identity, language policy, and globalization.